Jump to content

Using the Quotient Rule to Derive the Equation

Recommended Posts

Guest

Hello. I need help deriving this equation using the quotient rule. I'm having difficulty reaching the correct answer because I've no idea what I'm doing wrong.

Quotient Rule: (u'v - v'u) / (v2)

Equation to derive: (2x-3) / (x2)

What I did:

u= 2x-3       v= x2

u'= 2           v'= 2x

*sustituted into equation to get:

-( 2x2 - 6x) / x4

The answer should be - (2x - 6) / x3 What am I doing wrong?

 

Share this post


Link to post
Share on other sites

u= 2x-3 ,    u' =2

v= x^2 ,    v'=2x

Using quotient rule,

= (x^2(2) - 2x(2x-3))/x^4

= (2x^2- 4x^2 +6x )/x^4

= -2x^2+6x/ x^4

Which can be simplified as -(2x^2 -6x)/x^4

Seems like you got the correct answer here.. maybe the answer is wrong? 

I checked with cymath as well (http://www.cymath.com/answer.php?q=differentiate%20%20(2x-3)%20%2F%20(x2)), same answer. 

Share this post


Link to post
Share on other sites

You've got the right answer. you can divide the equation by x and you'll get 2x-6 divided by x3. Just divide through by x.

Cheers,

King112

Share this post


Link to post
Share on other sites

Create an account or sign in to comment

You need to be a member in order to leave a comment

Create an account

Sign up for a new account in our community. It's easy!

Register a new account

Sign in

Already have an account? Sign in here.

Sign In Now

×

Important Information

We have placed cookies on your device to help make this website better. You can adjust your cookie settings, otherwise we'll assume you're okay to continue.